MANAGEMENT AND ECONOMICS: STRATEGIES FOR ENHANCING CORPORATE COMPETITIVENESS - Sri Porwani; Abdullah Rasjid; Hendriansyah; Dora Indah Triana; Faridatul Munawaroh (Adisam Publisher, 2024)
The purpose of this study is to evaluate the effectiveness of management and economic strategies in improving the competitiveness of the company. This research method uses a literature review. The results show that management strategies integrated with economic principles improve operational efficiency and effectiveness. In particular, companies that apply sophisticated market analyses and economic theories in their decision-making process tend to be more adaptive to changing market conditions and have a higher degree of resilience to external disturbances. The involvement of economic theories, such as comparative advantage and elasticity analyses, is proven to assist firms in identifying strategic opportunities and allocating resources effectively, which contributes to an improved competitive position in the market. Overall, the integration of management and economic strategies was found to be the best practice in preparing firms for volatile global business dynamics, enabling improvements in financial performance and long-term sustainability. This study underscores the importance of a holistic approach in business strategy formulation to achieve competitive advantage and sustainable growth.